Estrogen and Progesterone Synthesis with Cellular Response in a C57BL/6 Mouse Model of Cuprizone-Induced Demyelination - Karayiğit, Mehmet Önder; Yarım, Murat (Acta Scientiae Veterinariae, 2018)
Background: Demyelination refers to the degradation or loss of myelin sheath. In demyelination model studies, it has been reported that demyelination is regressed by giving steroid hormones such as estrogen and progesterone. However, there are not many studies investigating the synthesis of these two hormones by the brain during demyelination and remyelination. Neurosteroids are steroid hormones synthesized by the brain independently from peripheral tissues. In this study, it was aimed to have knowledge about the synthesis of these two hormones by the brain in experimentally formed demyelination process in brains of C57BL/6 mice and their role in the cellular response formed in the region. Materials, Methods & Results: In the study, 36 C57BL/6 mice were used: 12 mice were fed normal diet for 12 weeks as control group (Group I); 12 of them were fed 0.2% cuprizone diet for 12 weeks (Group II) and 12 mice were fed normal diet for 4 weeks after feeding cuprizone diet for 8 weeks (Group III). At the end of the experiment, mice were perfused with 4% paraformaldehyde and brain tissues were blocked in paraffin. 6 μm-thick section was taken from each block. Sections were stained histologically with LFB staining and immunohistochemically with MBP staining in order to determine the demyelination in sections. All sections were also immunohistochemically stained with GFAP to detect astrocytes, with NG2 to detect young OPCs, with aromatase for estrogen synthesis and with 3βHSD antibodies for progesterone synthesis. At the end of the study, complete myelination was observed in group I, while severe demyelination was determined in group II as a result of blind evaluation of LFB and MBP staining by two pathologists. In group III, demyelination was found to be mild. In immunostaining with GFAP and NG2 antibodies, the number of GFAP and NG2 positive cells in Group II was found to be increased compared to the control group. The difference between these two groups was statistically significant (P < 0.01). In group III, the number of GFAP and NG2 positive cells were found to be increased compared to the control group; however, it was found to be lower than that in experimental group II (P < 0.01). In immunohistochemical staining with aromatase and 3βHSD antibody, there was no staining observed in the control groups. While an intense staining was observed in experimental group II, fewer glial staining was noticed in experimental group III when compared to the experimental group II. The difference between these two groups was found to be statistically significant (P ˂ 0.01). Discussion: Aromatase is an enzyme that converts testosterone into estrogen. On the other hand, 3βHSD is an enzyme that converts pregnenolone to progesterone. Expression of aromatase from tissues refers to the synthesis of estrogen and expression of 3βHSD refers to progesterone synthesis. In previous demyelination studies carried out with cuprizone, it has been reported that demyelination is regressed by giving estrogen and progesterone during demyelination. In the presented study, we observed that enzyme levels that catalyze the synthesis of estrogen and progesterone increased during demyelination. In the study, it was determined that estrogen and progesterone levels were increased in the region by enzymes released from the glial cells of the brain as a response to damage formed during demyelination. Interestingly, during the period in which cuprizone was excluded from the diet, it was observed that remyelination began to be formed again and that enzyme levels synthesizing these hormones started to decrease. These results suggested that estrogen and progesterone may be synthesized in the brain after a damage and may contribute to remyelination by initiating a number of cell to cell signaling steps.